A bone to pick-cellular and molecular mechanisms of bone pain in sickle cell disease - Gollamudi, Jahnavi; Karkoska, Kristine A.; Gbotosho, Oluwabukola T.; Zou, Wei; Hyacinth, Hyacinth I.; Teitelbaum, Steven L. (Frontiers in Pain Research, 2024)
The bone is one of the most commonly affected organs in sickle cell disease (SCD). Repeated ischemia, oxidative stress and inflammation within the bone is largely responsible for promoting bone pain. As more individuals with SCD survive into adulthood, they are likely to experience a synergistic impact of both aging and SCD on their bone health. As bone health deteriorates, bone pain will likely exacerbate. Recent mechanistic and observational studies emphasize an intricate relationship between bone remodeling and the peripheral nervous system. Under pathological conditions, abnormal bone remodeling plays a key role in the propagation of bone pain. In this review, we first summarize mechanisms and burden of select bone complications in SCD. We then discuss processes that contribute to pathological bone pain that have been described in both SCD as well as non-sickle cell animal models. We emphasize the role of bone-nervous system interactions and pitfalls when designing new therapies especially for the sickle cell population. Lastly, we also discuss future basic and translational research in addressing questions about the complex role of stress erythropoiesis and inflammation in the development of SCD bone complications, which may lead to promising therapies and reduce morbidity in this vulnerable population.